Local evaluation of the Tasmanian component of the National Suicide Prevention Trial—Preliminary learnings. (10th May 2020) - Smith, Laura; Purton, Terry; Auckland, Stuart; Lees, David; Mond, Jonathan
Abstract: Objective: Tasmania is one of the 12 Australian sites chosen to participate in the National Suicide Prevention Trial. The Centre for Rural Health, University of Tasmania, was contracted to conduct a local‐level, process evaluation of this initiative using a Participatory Action Research approach, with the objective of this article to summarise progress and key learnings from the local evaluation to date. Design: Empowerment and Utilisation‐Focus Evaluation theoretical approaches informed the conduct of process evaluation activities, within an overarching participatory action research approach. Setting: Three participating regions in Tasmania were included as follows: Launceston, the North‐West and Break O'Day. Participants: Working group members, service providers and other relevant stakeholders. Interventions: Mixed‐methods surveys, field observations and content analysis were conducted. Results: Survey results indicated that most working group members understood the concept of a "systems‐based" approach to suicide prevention. Most participants believed that working group structures/functions engaged community members with lived experience, while around half believed that these structures/functions facilitated relationships with local services and that working group action plans adequately addressed issues of capacity building and sustainability. Preliminary field data suggested that awareness raising, engagement and face‐to‐face capacity‐building activities focused on the wider community were preferred to activities targeting specific populations. Conclusion: These preliminary findings suggest ambivalence among key stakeholders concerning the application of a systems‐based approach to suicide prevention in regional areas of Tasmania. Consistent with a participatory action research approach, the findings will inform the evolution of trial site activity for the remainder of the trial and, in due course, the implementation of future such initiatives.